Finite element modeling of laminated composite plates with locally delaminated interface subjected to impact loading - Abo Sabah, Saddam Hussein Ali (2013)
This project report presents the finite element formulation for the investigation of the effects of interface imperfection on the impact behavior of a laminated composite plate. The interface condition between the laminas plays a very important role in the determination of the behavior of the composite laminates. If the bonding is imperfect, it has high possibility to delaminate progressively. Most of the previous studies on laminated composites were carried out adopting the assumption that the laminas are perfectly bonded. However, the existence of a perfect interfacial bond in a real laminated composite seems to be impossible. Therefore, this study aims to investigate the effect of localized interface imperfection on the behavior of a laminated composite plate when subjected to low velocity impact loading for various fiber orientations. A thin, flat, rectangular laminated plate with two layers of Eglass/ Epoxy transversely isotropic lamina and an orthotropic interface layer between them are considered in this study. The interface is modeled as a layer of zero thickness and zero mass, and the imperfection factor is applied locally to the interface. By using MATLAB, the stiffness matrix, mass matrix, and the impact force vector are formulated and programmed in order to obtain the deformation of the plate. The results show that as the separation of fiber orientation between the two laminas increases, both central deflection and energy absorption increase. The increase of delamination area leads to plate’s damage due to the increase in the absorbed energy, resulting in higher deformation.